Pengaruh Kesadaran Wajib Pajak, Kepatuhan Wajib Pajak, dan Pelayanan Perpajakan Terhadap Tingkat Pemahaman Wajib Pajak - Clemens Beremalp Gaga Leta; Kenny Ardillah (UNIVERSITAS KALBIS, 2022)
This study aims to find out how the effect of taxpayer awareness, taxpayer compliance, and tax services on the level of understanding of taxpayers carried out by research on taxpayers in the Kelapa Gading area. The population in this study is mandatory to invite private persons in Kelapa Gading. The sample taken by the author in this study were 100 taxpayers with the method of distributing questionnaires as a means of data collection. The data was taken in May 2021 and this data uses a quantitative approach. The results of the research through the distribution of questionnaires indicate that taxpayer awareness, taxpayer compliance and tax services affect the level of understanding of taxpayers about taxation on taxpayers in Kelapa Gading.